Diversity of Trichoderma species associated with green mold contaminating substrates of Lentinula edodes and their interaction - Cao, Zi-Jian; Zhao, Juan; Liu, Yu; Wang, Shou-Xian; Zheng, Su-Yue; Qin, Wen-Tao (Frontiers in Microbiology, 2024)
Introduction The contamination of Trichoderma species causing green mold in substrates poses a significant obstacle to the global production of Lentinula edodes, adversely impacting both yield and quality of fruiting bodies. However, the diversity of Trichoderma species in the contaminated substrates of L. edodes (CSL) in China is not clear. The purpose of this study was to assess the biodiversity of Trichoderma species in CSL, and their interactions with L. edodes. Methods A comprehensive two-year investigation of the biodiversity of Trichoderma species in CSL was conducted with 150 samples collected from four provinces of China. Trichoderma strains were isolated and identified based on integrated studies of phenotypic and molecular data. Resistance of L. edodes to the dominant Trichoderma species was evaluated in dual culture in vitro. Results A total of 90 isolates were obtained and identified as 14 different Trichoderma species, including six new species named as Trichoderma caespitosus, T. macrochlamydospora, T. notatum, T. pingquanense, T. subvermifimicola, and T. tongzhouense, among which, T. atroviride, T. macrochlamydospora and T. subvermifimicola were identified as dominant species in the CSL. Meanwhile, three known species, namely, T. auriculariae, T. paraviridescens and T. subviride were isolated from CSL for the first time in the world, and T. paratroviride was firstly reported to be associated with L. edodes in China. Notebly, the in vitro evaluation of L. edodes resistance to dominant Trichoderma species showed strains of L. edodes generally possess poor resistance to Trichoderma contamination with L. edodes strain SX8 relatively higher resistant. Discussion This study systematically investigated the diversity of Trichoderma species in the contaminated substrate of L. edodes, and a total of 31 species so far have been reported, indicating that green mold contaminated substrates of edible fungi were undoubtedly a biodiversity hotspot of Trichoderma species. Results in this study will provide deeper insight into the genus Trichoderma and lay a strong foundation for scientific management of the Trichoderma contamination in L. edodes cultivation.